Senam Tentang Diabetes Mellitus Di Puskesmas Bintuhan Desa Sinar Pagi Kelurahan Bandar Kecamatan Kaur Selatan Kabupaten Kaur - Putri, Mike Milo Diana; Noviza, Noviza; Sari, Dewi Putri Kemala; Pratiwi, Dian; Hermalena, Yeka; Lestari, Emi Kasih; Septinawati, Septinawati; Handayani, Seventri Herma; Surahman, Ferry; Rohani, Tuti; Sari, Fikitri Marya (Universitas Dehasen Bengkulu, 2025)
Diabetes Mellitus (DM) is a disease that has recently become more common. We also often refer to diabetes mellitus as diabetes or blood sugar disease. This disease is a type of chronic disease whose initial sign is an increase in blood sugar levels as a result of a disturbance in the body's metabolic system. The organ that is disturbed is the pancreas, which no longer functions as it should. The pancreas is no longer able to produce the hormone insulin to meet the body's needs. Good management of diabetes mellitus requires 4 main pillars, namely education, meal planning, physical exercise and pharmacological intervention. One of the recommendations for managing diabetes mellitus is to use physical exercise. One exercise that can be done by diabetes mellitus sufferers is diabetes mellitus exercise. Diabetes melltus exercises are carried out using rhythmic movements 3 times a week for 1 month with an exercise duration of 30-60 minutes Exercise or physical exercise is an initial effort to prevent, control and overcome diabetes. Physical exercise can directly cause increased use of glucose by active muscles, and more open capillary beds so that more insulin receptors are available to become more active, which will have an effect on reducing blood glucose in diabetes mellitus patients. One exercise that diabetes sufferers can do is diabetes gymnastics. Physical exercise can directly cause an increase in glucose usage so that more insulin receptors are available and become more active, which will have an effect on reducing blood glucose in DM patients, resulting in changes in blood sugar levels. Physical exercise in type 2 DM plays a major role in regulating blood sugar levels. Exercise can reduce anxiety about the disease, create a feeling of joy and more self-confidence and ultimately improve the quality of life even though he suffers from a chronic illness. Diabetes exercises are often done because these exercises can work all the organs of the human body, from the brain to the toes. Because the impact of diabetes attacks the entire body. The lightest impact is tingling in the feet. Meanwhile, the worst thing is suffering a stroke. The varied movements make the brain work to memorize them. Getting the brain used to working can improve memory and strengthen concentration. This is a therapy for mild strokes and prevents dementia. The importance of controlling blood sugar levels for diabetes sufferers is to avoid complications that can cause death.